Measurement of Social Strain in People with Dementia: A Preliminary Study of the Reliability and Validity of the Negative Relationship Quality Questionnaire in Indonesia - Vidyanti, Amelia Nur; Putri, Galenisa Falinda Santika; Fauzi, Aditya Rifqi; Nafiati, Rizqa; Prodjohardjono, Astuti; Effendy, Christantie (BioMedCentral, 2022)
People with dementia (PWD) may exhibit symptoms that negatively affect their relationships with their families or friends which could cause social strain. The Negative Relationship Quality (NRQ) questionnaire can be used to measure social strain in PWD. There has never been an Indonesian adaptation of the NRQ. This preliminary study aimed to measure the validity and reliability of the NRQ among PWD in Indonesia (NRQ-INA). This study used a cross-sectional design. Forward–backward translation methods were conducted first. Pearson’s correlation and factor analysis were employed for the validity test. Cronbach’s alpha and test–retest were used to determine reliability. The NRQ-INA has four parallel items related to social strain that are divided into three subscales and asked to spouse/partner, family members, and friends, leading to a total of 12 questions. The results of validity testing from 60 respondents showed that all items in the NRQ-INA were strongly valid with correlation coefficients (r) of >0.8 (p < 0.01). Factor analysis showed a convergence with the variance explained of more than 50% for all items in each subscale, which also indicated that NRQ-INA had acceptable construct validity to measure social strain. Cronbach’s alpha values (α) were 0.926, 0.942, and 0.938 for the subscales of spouse, friends, and family members, respectively. The correlations of test–retest reliability for all items were >0.7 (p < 0.01), demonstrating a reliable NRQ-INA measurement. In conclusion, NRQ-INA had a good validity and reliability to measure social strain in PWD. Further study of the concurrent validity among PWD is still needed.